Pharmacokinetic drug evaluation of palbociclib for the treatment of breast cancer. (2nd September 2018) - De Luca, Antonella; Maiello, Monica R.; D'Alessio, Amelia; Frezzetti, Daniela; Gallo, Marianna; Carotenuto, Marianeve; Normanno, Nicola
ABSTRACT: Introduction : Cyclin-dependent kinases (CDKs) 4 and 6 regulate the transition from G0/G1-phase to S-phase of the cell cycle and have been identified as key drivers of proliferation in hormone receptor (HR)-positive breast cancer. The CDK4/6 inhibitor palbociclib in combination with endocrine therapy has been approved for treatment of HR-positive/HER2-negative breast cancer patients. Areas covered : In this article, we provide an update of the data on pharmacodynamics, pharmacokinetics, preclinical, and clinical studies of palbociclib in breast cancer. We performed a search of data on palbociclib in the PubMed and the clinicaltrials.gov databases, in the FDA website and in the ASCO and AACR proceedings. Expert opinion : In order to optimize the clinical outcome of HR-positive breast cancer patients treated with palbociclib, predictive biomarkers allowing patient selection are urgently needed. A recent study suggested that early dynamics of PIK3CA mutations in circulating tumor DNA might be a potential predictive biomarker for CDK4/6 inhibitors. Several clinical trials are ongoing with the aim to explore the activity of combinations of palbociclib with targeted agents and/or immunotherapy in the different subtypes of breast cancer in both metastatic and early phases of the disease. These combinations might allow improving the sensitivity and overcoming mechanisms of resistance.